Measuring Sovereign Risk in Turkey : An Application of the Contingent Claims Approach - Keller, Christian (IMF Working Papers; Working Paper ;, 2007)
Improved macroeconomic conditions and changes to the asset-liability structure on Turkish balance sheets since the 2001 crisis have improved Turkey's overall sovereign risk profile. Nonetheless, the country remains subject to bouts of volatility, as evidenced most recently in the May/June 2006 market turbulence. This paper examines these changes in Turkey's risk profile using the Contingent Claims Approach (CCA), to quantify the evolution of Turkey's sovereign risk, relate risk indicators to market prices of risk, and conduct scenario analyses to assess the effects of potential market volatility and policy adjustments on key risk indicators.